(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
The distribution and abundance of soil microbes were studied under three different land uses (arable land, forest land and pasture land) in Michael Okpara University of Agriculture, Research and Teaching Farms, Umudike, Abia State to observe the impact of land use on fungi and bacteria populations. Soil samples were collected at 3 sampling points from each land use type at 0 – 20 cm depth. From the data collected, the populations of Bacillus and Aspergillus species showed some level of significance at 5%. The results of some soil properties studied revealed that the soil chemical properties and microbial distribution varied with land use systems. The total viable count of Bacillus population under forest land (18.00×103±8.72 CFU/g) was significantly (p<0.05) higher than pasture land (3.00×103±1.00 CFU/g) and arable land (8.67×103±3.79 CFU/g).Also, forest land was observed to have the highest total viable count of bacteria population of 1.52×105±0.84 CFU/g). Values of Aspergillus population was highest in arable land (1.33×103±0.58 CFU/g) but was statistically similar (p>0.05) to forest land and pasture land. Population of fungi was significantly the same in the different land use types. There was significant difference (p<0.05) in soil pH, with arable land giving the highest mean value of 5.4±0.17. Organic carbon content was highest in pasture (3.33±0.17) and forest land uses (3.10±0.79) and significantly (p<0.05) different from that of arable land (2.10±0.22). In this study, land use affected microbial population and also influenced organic matter content.